2021
DOI: 10.3390/toxins13040253
|View full text |Cite
|
Sign up to set email alerts
|

The Crystal Structure of Bacillus cereus HblL1

Abstract: The Hbl toxin is a three-component haemolytic complex produced by Bacillus cereus sensu lato strains and implicated as a cause of diarrhoea in B. cereus food poisoning. While the structure of the HblB component of this toxin is known, the structures of the other components are unresolved. Here, we describe the expression of the recombinant HblL1 component and the elucidation of its structure to 1.36 Å. Like HblB, it is a member of the alpha-helical pore-forming toxin family. In comparison to other members of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Ganash et al (2013) speculated that the Nhe trimer requires interaction with unknown proteins of an additional function [37]. A specific binding order of the three Nhe and Hbl components is also necessary for pore formation [51,52]. We found that NheB and Hbl-L 1 were close to NheA and Hbl-B in the predicted trimer structure.…”
Section: Discussionmentioning
confidence: 69%
“…Ganash et al (2013) speculated that the Nhe trimer requires interaction with unknown proteins of an additional function [37]. A specific binding order of the three Nhe and Hbl components is also necessary for pore formation [51,52]. We found that NheB and Hbl-L 1 were close to NheA and Hbl-B in the predicted trimer structure.…”
Section: Discussionmentioning
confidence: 69%
“…To assess the structural stability of modelled Cry48Aa1-Tpp49Aa1 complexes, molecular dynamics (MD) simulations were performed using GROMACS (v.2020.1) 47 on Cardiff University’s High-Performance Computing cluster, Hawk. Set-up, energy minimisation, equilibration, and production simulations were performed as previously described 48 . Production simulations were performed for 100 ns and the resulting trajectories were visualised.…”
Section: Methodsmentioning
confidence: 99%
“…HBL toxin comprises three subunits: HBL-B, HBL-L1, and HBL-L2, encoded by the genes hblA, hblD , and hblC , respectively. 13 , 14 These three genes are located on the operon hblCDAB , and the promoter is located upstream of hblC . 15 Alignment of the deduced amino acid sequences of the three proteins indicates significant similarity (20 to 24% identical), and structural analysis of the HBL protein shows that all three components are almost entirely composed of α-helices.…”
Section: Introductionmentioning
confidence: 99%